Implementation of Family-Based Disease Management Model through Community Empowerment - Murniati Muchtar; Lola Felnanda Amri; Tasman Tasman; Syafrisar Meri Agritubella (Universitas Muhammadiyah Semarang, 2022)
Efforts to improve the degree of public health are carried out by applying various approaches, including involving the potential of the community in disease management with a family approach. The purpose of this study was to analyse the effect of implementing family empowerment models on increasing family knowledge about healthy families in Nanggalo Padang. The research design was Quasy Experiment research, one group pretest and posttest design. The sample in the study was 30 people using the purposive sample technique in their families who visited Posyandu in 3 villages, namely, Gurun Laweh, Kurao Pagang and Surau Gadang Villages. The community empowerment model used is the Family-Based Disease Management Model developed by Mardikanto. The result showed that there was an effect of the application of the community empowerment model on family knowledge about healthy families (p-value = 0.000). The recommendation of this study is that it is necessary to periodically evaluate the understanding and knowledge of health and family cadres for indicators of healthy families in the community.